Air Bersih bagi Masyarakat Pinggir Sungai Bandar Jaksa Tanjung Balai - Eswanto, Eswanto; Siman, Siman; Hutauruk, Denny Meisandy; Pasaribu, Muhammad Nuh Hudawi; Putri, Puput Widiasa; Siagian, Tony (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Gading sub-district is in Datuk Bandar Tanjung Balai sub-district. In Gading sub-district there is Bandar Prosecutor River which flows into the Asahan River. So far, the people who live around that location have taken water from this river to meet their needs. The problem is that the water they consume is not suitable (smelly water, dark color when it rains, mossy). This activity aims to help partners' problems with the installation of water purification equipment. The implementation method begins with assessing the shortcomings of river water purification technology, then a site survey, equipment installation, and unit handover. The results of implementing this service have been realized at partner locations, clean water has been enjoyed by community. The standard of social life, especially the provision of clean water suitable for consumption for cooking, bathing, washing clothes and other needs, can be helped by this service where there are no similar activities in that location.